تصميم وتنفيذ نظام مراقبة وتحكم مُبرمج بعمل قبانات قسم مطاحن المواد الأولية في شركة طرطوس لصناعة الاسمنت - ابراهيم, ثائر; جوهره, أحمد (Latakia University Journal -Engineering Sciences Series, 2017)
تُشكل القبانات جزء أساسي في أي منشأة إنتاجية،حيث يُعتبر نظام التحكم بها ومراقبة عملها من الأمور الهامة التي يجب أن تتصف بالدقة والموثوقية. انطلاقا من ذلك سنقوم في هذا البحث بمحاولة تطوير نظام التحكم والمراقبة الخاص بقبانات التغذية لقسم مطاحن المواد الأولية في شركة طرطوس لصناعة الاسمنت ومواد البناء الغير موثوق. سيتمحور العمل على محاولة تلافي الأخطاء والمشاكل التي يعاني منها نظام التحكم القديم بهدف الوصول إلى أفضل أداء ممكن للقبان وتسهيل عملية الصيانة وكشف العطل فور حدوثه، وذلك من خلال اقتراح قبانات مُقادة بواسطة المتحكمات المنطقية القابلة للبرمجة من شركة SIEMENS ذات المعالج (CPU 315-2 PN/DP) وتصميم نظام مراقبة وتحصيل المعطيات باستخدام البرمجية (WINCC Flexible sp3 2008).سنقوم بإسقاط خطوات الدراسة بشكل عملي على قبان التغذية الخاص بمطحنة المواد الأولية، وسنجري الاختبارات اللازمة للتأكد من صحة ودقة نظام التحكم الجديد وبالتالي مدى وثوقيته.The weigh feeders constitute an essential part of any production facility, where its control and supervision system is one of the important things that should be characterized by precision and reliability.From this research we will try to develop the unreliable control and supervision system of the weigh feeders in mills of raw materials department in Tartous cement and building materials company. The work Will focus on trying to avoid errors and problems that the old control system suffered in order to reach the best possible performance of weigh feeders, facilitate maintenance process and reveal the problems as they happen by proposing controlled weigh feeders by programmable logical controllers from SIEMENS corporation with processor (CPU 315-2 PN / DP), and design supervision and collection data system using software (WINCC Flexible sp3 2008).We'll apply the steps of the study practical on the weigh feeder of mill of raw materials, and we will conduct the necessary tests to ensure the validity and accuracy of the new control system, therefore the range of reliability.